Meta Analysis – Effect of Occupational Noise on the Risk of Hypertension and Noise Induced Hearing Loss in Industrial Workers - Ila Izzatus Salamah; Sumardiyono Sumardiyono; Bhisma Murti (Masters Program in Public Health, 2023)
Background: Noise is defined as sound intensity that is unwanted and can pose risks to health and safety at work, such as the risk of hypertension and noise-induced hearing loss. This study aims to analyze the effect of occupational noise on the risk of hypertension and noise induced hearing loss in industrial workers.Subjects and Method: A systematic review and meta-analysis was carried out using the PRISMA guidelines and the PICO model. Population: industrial workers. Intervention: occupational noise exposure ≥85 dB. Comparison: occupational noise exposure <85 dB. Outcome: hypertension and noise induced hearing loss. Articles are collected from PubMed, Science Direct, and Google Schoolar. The keywords used “occupational noise and hypertension” OR “occupational noise and hearing loss” AND “occupational noise” OR “hypertension” AND “hearing loss” AND “cross sectional study”. A total of 13 articles met the inclusion criteria, namely primary full text paper, cross-sectional study design, with a relationship size adjusted Odds Ratio (aOR), labor research subjects, interventions in the form of exposure to noise ≥85 dB and outcomes in the form of hypertension and noise induced hearing loss for meta-analyses were then assessed using RevMan 5.3.Results: Meta-analysis included 13 cross sectional studies from China, Brazil, Ethiopia, Jordan, South Africa, Thailand, Kuwait, and Pakistan. Occupational noise ≥85 dB significantly increased the risk of hypertension (aOR= 2.07; 95% CI= 1.31 to 3.26; p= 0.002) and hearing loss (aOR= 1.97; 95% CI= 1.36 to 2.85; p= 0.003) than occupational noise <85 dB.Conclusion: Occupational noise ≥85 dB increases the risk of hypertension and hearing loss in industrial workers. Keywords: occupational noise, hypertension, hearing loss, workers Correspondence:Ila Izzatus Salamah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: ilaizzatus31@gmail.com. Mobile: +62858868132490.